Polar Silk Road: a China’s Ambitious Plan of Belt and Road Initiative in Arctic Region (مجلة الواحات للبحوث والدراسات, 2025)
The Arctic area has recently gained special attention owing to climate change and the melting of ice; a fact that has attracted China's interest. To find new routes and connect Europe with Asia, Beijing is looking for transportation corridors to attain the objectives of its project, the Belt and Road Initiative (BRI). Consequently, China has introduced a strategy known as the Polar Silk Road (PSR) as a means to carry out its work in the Arctic. Within this context, the present article essentially seeks to determine the major opportunities provided by the development of the PSR. It equally sheds light on the responses of the US and Russia to this project. The descriptive and qualitative methods are, accordingly, implemented to explain the strategic benefits that China is likely to obtain from this strategy. The paper concludes that China intends to maintain and reinforce its influential role through the PSR strategy, striving for a prosperous and environmentally conscious future for the Arctic area.Keywords: Belt and Road Initiative, China, Polar Silk Road Strategy, Russia, US.